Milk Fat Globule-EGF Factor 8 Attenuates Neutrophil Infiltration in Acute Lung Injury via Modulation of CXCR2 - Aziz, Monowar (2012)
Excessive neutrophil infiltration to the lungs is a hallmark of acute lung injury (ALI). Milk fat globule-EGF factor 8 (MFG-E8) was originally identified for phagocytosis of apoptotic cells. Subsequent studies revealed its diverse cellular functions. However, whether MFG-E8 can regulate neutrophil function to alleviate inflammation is unknown. We therefore aimed to reveal MFG-E8 roles in regulating lung neutrophil infiltration during ALI. To induce ALI, C57BL/6J wild-type (WT) and Mfge8(−/−) mice were intra-tracheally injected with LPS (5 mg/kg). Lung tissue damage was assessed by histology and the neutrophils were counted by a hemacytometer. Apoptotic cells in lungs were determined by TUNEL, while caspase-3 and MPO activities were assessed spectrophotometrically. CXCR2 and GRK2 expressions in neutrophils were measured by flow cytometry. Following LPS challenge, Mfge8(−/−) mice exhibited extensive lung damage due to exaggerated infiltration of neutrophils and production of TNF-α, MIP-2 and MPO. Increased number of apoptotic cells was trapped into the lungs ofMfge8(−/−) mice than WT mice, which may be due to insufficient phagocytosis of apoptotic cells or increased occurrence of apoptosis through the activation of caspase-3. In vitro studies using MIP-2 mediated chemotaxis, revealed higher migration of neutrophils of Mfge8(−/−) mice than WT mice via increased surface exposures to CXCR2. Administration of recombinant mouse (rm)MFG-E8 reduces neutrophil migration through up-regulation of GRK2, and down-regulation of surface CXCR2 expression. Conversely, these effects could be blocked by anti-α(v)-integrin antibodies. These studies clearly indicate the importance of MFG-E8 in ameliorating neutrophil infiltration and suggest MFG-E8 as a novel therapeutic potential for ALI.